Views on the judicial system of the Russian Empire: topical issues - Александров, Олексій Володимирович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2010)
The article analyzes the views of the famous Ukrainian writer, lawyer Alexander Konisskyi (1836-1900) on the judicial system of the Russian Empire, based on his publications in periodicals. He attracted public attention to issues related to professional education by selecting the judges, with the activity of juries, an improvement of the judicial institution's activity.